MANAJEMEN LABA DALAM PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY DAN PENGARUHNYA PADA RETURN SAHAM - Krisna, Dhyana Sari; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2015)
This study aims to determine the effect of earnings management in the implementation of CSR and its impact on stock returns property and real estate companies listed on IDX 2011-2013. The study sample as many as 48 with purposive sampling technique. Data analysis in this study using path analysis. Based on the results of the analysis found that the significant negative effect of earnings management on CSR. Significant negative effect of earnings management on stock returns. CSR is a significant positive effect on stock returns. Significant negative effect of earnings management on stock returns through CSR. The existence of a negative and significant effect between earnings management with CSR, stakeholders are expected to make disclosure of CSR as a managerial tool to see an indication of whether the company made profit management or not. Influential CSR with stock returns indicates that the disclosure of information in the company's CSR can attract investors. Therefore, it is expected the company can improve its CSR activities and also improve the quality of disclosure in order to better corporate image .
Keywords: earnings management, CSR, stock return